Otredades y permanencias: fotografía histórica y exposición contemporánea del bosque y el indígena amazónico - La Serna Salcedo, Juan Carlos (2018)
The renewed interest that historical photography of the Peruvian Amazon has awakened in the social sciences and cultural and artistic projects encouraged us to explore the importance that these images, produced between the late 19th and the early 20th century, have acquired in the construction of a contemporary narrative regarding the Amazonian indigenous peoples and the Amazonian forest. The analysis of these photographs is even more relevant in the current setting, marked by the public debate emerged at the increasing pressure that the Peruvian government and external agents have on the Amazon region and its natural resources. In this regard, early visual representations of the Amazonian indigenous peoples and the Amazonian forest, shown in recent photo exhibitions, allow us to reflect on how the Amazon is being integrated into contemporary national imaginary.